Determinants of Impulse Buying by the Younger Generation in E-Commerce: A Behavioral Study in the Context of SDGs 12 - Avril Nur Shefi (Journal of Psychology and Culture Behavior in SDGs, 2025)
Objective: The purpose of this study is to analyze the determinants of impulsive buying among young people in e-commerce, particularly among 12th grade social studies students at SMAN 1 Driyorejo. The research focuses on the influence of celebrities' authenticity, sentiment polarity, and impulse buying tendency on the urge to buy impulsively, as well as the role of impulse buying tendency as a moderating variable. Method: Using a quantitative approach and Partial Least Squares Structural Equation Modelling (PLS-SEM) analysis techniques through WarpPLS software, data was obtained from 106 respondents through questionnaires. Results: The results show that celebrities' authenticity has a significant effect on the urge to buy impulsively, and sentiment polarity also has a significant effect on the urge to buy impulsively. Furthermore, impulse buying tendency was found to moderate the relationship between celebrities' authenticity and the urge to buy impulsively, as well as the relationship between sentiment polarity and the urge to buy impulsively. Novelty: This study focuses on the context of young learners in Indonesia, who are a segment of the population with Gen Z characteristics. With a local background and a comprehensive approach relevant to the development of marketing and consumer education strategies in the digital age. The findings support SDG 12 by encouraging responsible consumption through media literacy and sustainable digital behavior.